Morphophysiological Responses of Oat (Avena sativa L.) Genotypes from Pakistan’s Semiarid Regions to Salt Stress - Khan, Abbas; Afridi, Muhammad Zahir; Zia, Adil; Mihoub, Adil; Saeed, Muhammad Farhan; Abbas, Musawer; Jamal, Aftab (Journal of Scientific Agriculture, 2023)
Soil salinity is a major constraint to modern agriculture, with around 20% of the previously irrigated area becoming salt affected. Identifying suitable salt stress-tolerant genotypes based on their agronomic and physiological traits remains a herculean challenge in forage-type Oat (Avena sativa L.) breeding. The present study was designed to investigate the response of oat crop plants against the salt (NaCl) stress in Mardan, Pakistan. The experiment was carried out in complete randomized design (CRD) with two factors trail comprising of the performance of four different genotypes of oat (NARC oat, PARC oat, Green Gold and Islamabad oat) in response to four levels of saline stress (0, 25, 50 and 75 mmol L-1 NaCl). Plant growth and physiological parameters including germination (G, %); fresh shoot weight (FSW, g); fresh root weight (FRW, g); chlorophyll-a, chlorophyll-b, total chlorophyll, and total carotenoids were analyzed for identifying salt tolerance. Germination (%) of oat genotypes was negatively affected by higher salt stress. Mean values showed that maximum germination (57.5%) was recorded for control while minimum germination (48.75%) was recorded for 25 mmol L-1 NaCl and that maximum germination (58%) was recorded for PARC oat. The root and shoot fresh weight of all genotypes declined with increasing salt stress, while NARC and Green Gold oat showed considerably higher values than the other genotypes. Although chlorophyll and carotenoids were found to be negatively affected by increasing salt concentrations, NARC and Green Gold oat genotypes performed considerably better at 75 mmol L-1 NaCl when compared to the other genotypes. Based on the mean shoot dry weight ratio ± one standard error, the four Oat genotypes were categorized as salt-tolerant (Green Gold), moderately tolerant (PARC and NARC), and salt-sensitive (Islamabad). The more salt-tolerant genotype (Green Gold) demonstrated relatively high salinity tolerance and may be useful for developing high-yielding oat hybrids in future breeding programs under salt stress conditions.